2007
DOI: 10.1253/circj.71.390
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of Arrhythmogenic Substrates and Vulnerability to Ventricular Tachycardia in Left Ventricular Hypertrophy in Salt-Sensitive Hypertensive Rats

Abstract: ypertensive left ventricular hypertrophy (LVH) is associated with an enhanced incidence of ventricular arrhythmia and an increased risk of sudden cardiac death. [1][2][3] Although in vitro studies of hypetensive LVH have proposed various electrophysiological abnormalities (ie, impulse formation 4,5 and conduction, 6-8 and repolarization abnormalities 9 ) as arrhythmogenic substrates, it remains unclear how these factors directly relate to the vulnerability to ventricular tachyarrhythmia in the in vivo whole he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The simulated slowing of conduction velocity was consistent with published data on electrical remodeling in LVH in animals and humans, [17][18][19][20][21][22] and we have shown that the conduction velocity slowing in the left ventricle by 30% in the Purkinje fiber net and by 50% in the working myocardium resulted in an increase in QRS amplitude in all simulated cases including the reference heart. 9 In this simulation study, 9 we also showed that anatomical types of hypertrophy and conduction slowing have different effect on ECG-LVH criteria.…”
Section: Increased Qrs Voltagesupporting
confidence: 89%
“…The simulated slowing of conduction velocity was consistent with published data on electrical remodeling in LVH in animals and humans, [17][18][19][20][21][22] and we have shown that the conduction velocity slowing in the left ventricle by 30% in the Purkinje fiber net and by 50% in the working myocardium resulted in an increase in QRS amplitude in all simulated cases including the reference heart. 9 In this simulation study, 9 we also showed that anatomical types of hypertrophy and conduction slowing have different effect on ECG-LVH criteria.…”
Section: Increased Qrs Voltagesupporting
confidence: 89%
“…11,18,24,34 We also observed that the enhancement of these proarrhythmic parameters during TH (30°C) was associated with an increased number of PSs (ie, wavebreaks) during S1 pacing and VF. These findings suggest that these accumulated proarrhythmic parameters during TH (30°C), either via a single dominant factor (such as SDA) or by a synergistic effect of multiple coexisting factors, contribute to the occurrence of wavebreaks during S1 pacing, leading to increased vulnerability to pacing-induced VF.…”
Section: Proarrhythmic Parameters and Wavebreaks During Th (30°c)mentioning
confidence: 59%
“…The exact nature of true electrical remodeling in LVH has been the subject of active investigation 43 , and is likely to largely explain the observed differences between electrical and anatomic LVH. These altered electrophysiological properties of the myocardium seem to be somewhat independent from the morphological transformations in LVH 29 , and may serve as a substrate for triggering and maintaining ventricular arrhythmias 44 . In some experimental models, reduced Cx43 expression has been associated with diminished QRS amplitudes 41, 45 , a phenomenon that along with extracardiac factors may partly explain the common “false negative” results of ECG in diagnosing anatomic LVH.…”
Section: Myocardial Cellular Electrical and Interstitial Remodelingmentioning
confidence: 99%